2022
DOI: 10.1177/23743735221112208
|View full text |Cite
|
Sign up to set email alerts
|

A Multiple Stakeholder Perspective on the Impact of COVID-19 on Dementia Care

Abstract: The aim of this study was to describe the impact of the COVID-19 pandemic on dementia care from a multiple stakeholder perspective. We used a multi-method design, with a cross-sectional survey followed by focus groups/interviews. Surveys were completed by people living with dementia (n  =  27), family caregivers (n  =  161), and health and social care professionals (n  =  77). A sub-sample (n  =  55) participated in an interview or one of 9 focus groups. Surveys were analyzed with descriptive statistics and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Communication difficulties with HCBS and institutional facilities undermined caregivers’ care access and oversight, eroded trust in medical facilities, and altered care decision-making. Our findings corroborate literature showing the pandemic worsened caregiver burden through loss of usual caregiving supports and interference with care quality monitoring (Simard & Volicer, 2020; White et al, 2022). Policy fluctuations and routine disruptions further complicated caregivers’ formal care oversight, making caregivers assume additional responsibilities, with greater risk of adverse health outcomes (Masoud et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Communication difficulties with HCBS and institutional facilities undermined caregivers’ care access and oversight, eroded trust in medical facilities, and altered care decision-making. Our findings corroborate literature showing the pandemic worsened caregiver burden through loss of usual caregiving supports and interference with care quality monitoring (Simard & Volicer, 2020; White et al, 2022). Policy fluctuations and routine disruptions further complicated caregivers’ formal care oversight, making caregivers assume additional responsibilities, with greater risk of adverse health outcomes (Masoud et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Decreased physical and social activities can compound cognitive and physical decline and increase mortality (Simard & Volicer, 2020). Furthermore, COVID-19 exacerbated caregiver burden by worsening access to healthcare providers and causing loss of usual caregiving supports (White et al, 2022). Pandemic-related economic stresses like unemployment also threatened caregivers’ ability to provide care (Falk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, qualitative research that specifically addresses this topic is scarce. The majority of studies examine, more broadly, the experiences of people with dementia and their carers during the pandemic and often note an increase in their use of digital technologies to engage with formal health and social care services 30–33 . Although Giebel et al 34 found that those unpaid carers and people with dementia that accessed digital support during this period reported these services to be of poorer quality and less effective than in‐person contact.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest the need to implement specific programs for caregivers to learn “coping” skills, socialization, support groups, online interventions to reduce stress, anxiety and depression [ 37 , 44 , 45 , 46 ]. A rigorous examination is also required to detect caregivers with symptoms of anxiety, depression, or burnout, particularly in females and caregivers co-living with the patient where apparently the risk is higher [ 27 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%